A generic ontology methodology and factors to address design consistency - Yew, K.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
Domain ontology is a knowledge model for computer reasoning. Hence, the quality of an intelligent application is affected by the quality of its ontology. The quality of an ontology can be affected by methodology used to develop it. Yet, ontology methodology is more of a craft than an engineering. This situation is discomforting and hopefully years of ontology development have come up with a more solid methodology backed by principles similar to software engineering. This article provides an analysis of a generic methodology for ontology development and factors affecting development of an ontology. Â© 2015 IEEE.